A Novel Approach for Visualizing Mixing Phenomena of Reactive Liquid-Liquid Flows in Milli- and Micro-Channels - Frey, Torben; Kexel, Felix; Dittmer, Kayla Reata; Bohne, Sven; Hoffmann, Marko; Trieu, Hoc Khiem; Schlüter, Michael (Frontiers in Chemical Engineering, 2022)
Modular milli- and micro-structured systems represent a promising approach to exploit the potential of micro-process technology, including precise reaction control and scale-up. A major drawback of micro-structured devices is fouling and mixing mechanisms need to be investigated phenomenologically to better understand the processes that lead to fouling. Most recent optical measurement methods rely on the detection of a single compound in mixtures. In case of reactive mixing, the state of the art procedures to locally visualize micro mixing relie\sout{s} on tracking a reaction product which forms on molecular scale. In literature, only small micro-structures are manufactured from transparent materials, however larger milli-structures often lack optical accesses with sufficient quality. Selective laser-induced etching (SLE) is a new technique which enables the fabrication of larger milli-structures in transparent materials that are relevant for industry-scale applications. This work develops a method based on a concept of Kexel et al. (2021) visualizing the selectivity of a competitive-consecutive gas-liquid reaction in a Taylor bubble flow. The main goal of this work is the analysis of the absorbance spectra of bromothymol blue (BTB) at different pH values in a miscible liquid-liquid system in a fused silica split-and-recombine mixer. The milli-structure of the mixer is manufactured by means of SLE. Backlight at different wavelengths is pulsed matching the recording frequency. In contrast to conventional UV/Vis setups, the absorbance is recorded locally within the mixer. The proposed method yields the 2D concentration distribution of multiple species with high spatial resolution. The spatially resolved reactant and product distribution unveils micro mixing and can yield important information about local root causes of fouling.